Industrial Organization, Trade, and Social Interaction : Essays in Honour of B. Curtis Eaton - Dow, Gregory K., 1954-; Eckert, Andrew, 1972-; West, Douglas Scott, 1953- (Book collections on Project MUSE., 2010)
"B. Curtis Eaton is one of Canada's leading microeconomists. As an applied economic theorist, Eaton has contributed greatly to industrial organization literature and has also worked in labour economics, economic geography, and organizational theory. The essays in this volume, by former students and present and former colleagues, call attention to the path-breaking work of Professor Eaton. The first two chapters provide a short overview of Eaton's research contributions and argue that his work laid the foundation for important research programs across the country. The remaining chapters, including an unpublished paper by Eaton himself, consist of original work that can be divided into the three broad categories of industrial organization and spatial competition, trade and productivity, and social interaction. Not only a collection of laudatory essays, Industrial Organization, Trade, and Social Interaction presents cutting edge research by leading scholars."--Jacket.